Do Not Leave Your Pricing Strategy Hanging: The Elevate Hammock Company. (October 2019) - Walker, Deborah; Walls, Simon; Junggren, Greyson; Gerdts, Nicholas
Greyson Junggren had an entrepreneurial spirit and started Elevate Hammock Company while he was still in college. His mission was to produce high-quality, durable hammocks that were made for the outdoors. Not knowing a lot about how to set the price for his hammocks when he first started his business, Greyson used a cost-plus/competitive approach. But after some time, he noticed that much of the market he had hoped to capture was staying with his higher priced competitors. While still generating and growing sales figures, Elevate Hammock Company was not capturing as much business from rival hammock companies in retail stores that Greyson expected and wanted. Greyson started to understand there was probably a real problem with his price when a very successful retailer in Taos, New Mexico ignored Greyson's suggested retail price of US$55.00 and instead raised the price to US$65.00; and this resulted in an increase in the demand for Greyson's hammocks. After 2 years in business, Greyson wondered if he should change his pricing strategy or his distribution model. What pricing strategy should he change to? And what other business strategies should he change or continue with if he did change his pricing strategy?